2022
DOI: 10.1038/s41467-022-33139-6
|View full text |Cite
|
Sign up to set email alerts
|

Infralimbic medial prefrontal cortex signalling to calbindin 1 positive neurons in posterior basolateral amygdala suppresses anxiety- and depression-like behaviours

Abstract: Generalization is a fundamental cognitive ability of organisms to deal with the uncertainty in real-world situations. Excessive fear generalization and impaired reward generalization are closely related to many psychiatric disorders. However, the neural circuit mechanism for reward generalization and its role in anxiety-like behaviours remain elusive. Here, we found a robust activation of calbindin 1-neurons (Calb 1) in the posterior basolateral amygdala (pBLA), simultaneous with reward generalization to an am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 71 publications
1
9
1
Order By: Relevance
“…Our data showed that activation of the DP/DTT increased anxiety-like behavior in the OFT and EPM. A considerable body of work implicates the rodent mPFC in the regulation of anxiety-like behavior [7,13,[22][23][24][25][26][27][28][29]86,[14][15][16][17][18][19][20][21], with contradictory findings supporting anxiogenic [18][19][20][21][22][23][53][54][55] or anxiolytic [24][25][26][27] roles. Manipulations selective to the vmPFC/IL also see conflicting effects on EPM and open field performance [21,24,26,60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data showed that activation of the DP/DTT increased anxiety-like behavior in the OFT and EPM. A considerable body of work implicates the rodent mPFC in the regulation of anxiety-like behavior [7,13,[22][23][24][25][26][27][28][29]86,[14][15][16][17][18][19][20][21], with contradictory findings supporting anxiogenic [18][19][20][21][22][23][53][54][55] or anxiolytic [24][25][26][27] roles. Manipulations selective to the vmPFC/IL also see conflicting effects on EPM and open field performance [21,24,26,60].…”
Section: Discussionmentioning
confidence: 99%
“…The medial prefrontal cortex (mPFC) is a key brain region involved in high-order functions such as attention [1,2], decision making [3,4], working memory [5,6], social behavior [7][8][9][10], mood [11,12] and anxiety [7,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. The mPFC integrates inputs from cortical sensory and motor systems, as well as subcortical brain structures [31][32][33][34][35][36] toward top-down control of output structures such as the amygdala, thalamus, hypothalamus and bed nucleus of the stria terminalis (BNST) [31,34,[36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the mPFC has been shown to suppress depression-induced amygdala-mediated hyperactive affective responses by recruiting BLA inhibitory interneurons (Rosenkranz and Grace, 2001 ; Bertholomey et al, 2022 ). Evidence has shown that the activation of Ventromedial prefrontal cortex (vmPFC)–pBLA inputs diminishes chronic unpredictable mild stress- (CUMS-) induced depression- and anxiety-like behaviors via activation of the pBLA Calb1 neuron (Yu et al, 2022 ). These results suggest that mPFC–BLA innervation regulates affective disorders in a BLA inhibition-dependent manner and that depression-like behavior may be associated with a circuit.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic resulted in a significant increase in depression and anxiety cases within a year 2 . Chronic stress is the principal environmental factor that triggers a decline in mood, leading to depression and anxiety 3 .…”
Section: Introductionmentioning
confidence: 99%